2002
DOI: 10.1104/pp.009019
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Aquaporins Play a Significant Role during Recovery from Water Deficit

Abstract: The role of plasma membrane aquaporins (PIPs) in water relations of Arabidopsis was studied by examining plants with reduced expression of PIP1 and PIP2 aquaporins, produced by crossing two different antisense lines. Compared with controls, the double antisense (dAS) plants had reduced amounts of PIP1 and PIP2 aquaporins, and the osmotic hydraulic conductivity of isolated root and leaf protoplasts was reduced 5-to 30-fold. The dAS plants had a 3-fold decrease in the root hydraulic conductivity expressed on a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
279
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(299 citation statements)
references
References 56 publications
(16 reference statements)
15
279
1
4
Order By: Relevance
“…Different research groups reached different conclusions on the function of PIP proteins. It has previously been reported that OsPIP1-1 and OsPIP1-3 had ability to transport water in the Xenopus oocytes [30,32], but other studies showed that only PIP2 proteins showed a rapid water transport activity, whereas PIP1s had no or a low water transport activity in the Xenopus oocytes [28,39]. Our data indicated that the transgenic plants over-expressing OsPIP1-1 or Os-PIP2-2 showed high tolerance to mild salt stress ( Figure 6C and 6D), suggesting that OsPIP genes play important roles in regulating water homeostasis, and that both OsPIP1-1 and OsPIP2-2 could possibly have intrinsic water transport ability in planta, which needs to be further confirmed biochemically in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…Different research groups reached different conclusions on the function of PIP proteins. It has previously been reported that OsPIP1-1 and OsPIP1-3 had ability to transport water in the Xenopus oocytes [30,32], but other studies showed that only PIP2 proteins showed a rapid water transport activity, whereas PIP1s had no or a low water transport activity in the Xenopus oocytes [28,39]. Our data indicated that the transgenic plants over-expressing OsPIP1-1 or Os-PIP2-2 showed high tolerance to mild salt stress ( Figure 6C and 6D), suggesting that OsPIP genes play important roles in regulating water homeostasis, and that both OsPIP1-1 and OsPIP2-2 could possibly have intrinsic water transport ability in planta, which needs to be further confirmed biochemically in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…First, it may be noted that the amino acid residues predicted to border the selectivity filter are the same in PIP1 and PIP2 members (exemplified in Table 1 for PsPIP1-1 and PsPIP2-1). Secondly, recent studies in which the expression of PIP1 members was either impaired or enhanced have provided strong evidence that PIP1 members function in cellular and whole-plant water relations (Siefritz et al, 2002;Martre et al, 2002;Aharon et al, 2003).…”
Section: Abundant Transcripts Of a Pip1 Homologue In The Dry Seedmentioning
confidence: 99%
“…Diurnal changes in root hydraulic conductance have been ascribed to changes in plasmalemna or tonoplast aquaporins that act as water channels controlling water fluxes between cells [96,129]. At leaf level, irradiance dependence of K L was found to be also driven by aquaporins or hydrogel effect on extravascular (and/or vascular) tissues [145].…”
Section: Drought Effects: Species Diversity Xylem Plasticity and Chamentioning
confidence: 99%